A THEOLOGICAL AND ETHICAL REFLECTION ON DIGITAL ECCLESIOLOGY FROM AN AFRICAN PERSPECTIVE - Isaac Boaheng; Kumasi Kumasi (Universitas PGRI Madiun, 2022)
: In the heat of the Covid-19 pandemic, many church leaders were compelled to use digital information and communication technology to maintain their presence and fellowship with their followers and other believers. The unprecedented incorporation of media technology into the church’s structures and activities (due to the pandemic) has brought about the urgent need to explore the nature and quality of this digitally-mediated presence from a theological and ethical perspective. The purpose of this paper, therefore, is to identify and concretely address key theological and ethical issues emerging from the church’s current digital experimentation with technologically-mediated worship. The paper uses a literature-based approach to critically examine data on digitally-mediated services obtained from journal articles, theses/dissertations and books. The main argument is that although digitally-mediated Christian ministry has theological, biblical and historical foundations, it is not appropriate (under normal circumstances) to replace offline church services with online church services. Therefore, the use of the digital space must complement (but not replace) the use of the analogue space for Christian ministry. This is very important especially in the African context where illiteracy rate is high and majority of the people do not have reliable access to electricity and internet facilities. The paper ends with recommendations for the post-pandemic church in its quest to navigate between the digital and analogue spaces in its operations.